58.9k views
1 vote
A function f is given by

f(x)equals=StartFraction 1 Over left parenthesis x plus 5 right parenthesis squared End Fraction 1(x+5)2.
This function takes a numbe x, adds
55,
squares the result, and takes the reciprocal of that result.
a) Find
f(22),
f(0), f(a),
f(tplus+22),
f(xplus+h), and
Start Fraction f left parenthesis x plus h right parenthesis minus f left parenthesis x right parenthesis Over h End Fraction f(x+h)-f(x)h.
b) Note that f could also be given by
f(x)equals=StartFraction 1 Over x squared plus 10 x plus 25 EndFraction
1×2+10x+25
Explain what this does to an input number x.

1 Answer

3 votes

Answer:


\mathbf{f(22) = (1)/(729)}


\mathbf{f(0) = (1)/((25))}


\mathbf {f(a) = (1)/((a+5)^2)}}


\mathbf{f(t+22) = (1)/((t+27)^2)}


\mathbf{f(x+h) = (1)/((x+h+5)^2)}


(f(x+h)-f(x))/(h)=
\mathbf{ (-h-2x-10)/((x+h+5)^2(x+5)^2)}

Explanation:

The mathematical interpretation of the A function f is given by

f(x)equals=StartFraction 1 Over left parenthesis x plus 5 right parenthesis squared End Fraction 1(x+5)2 is :


f(x) = (1)/((x+5)^2)

So; we are ask to find the following:

a)

f(22) ; i.e what is the function when x = 22

So replacing x = 22 into the above function; we have:


f(x) = (1)/((x+5)^2)


f(22) = (1)/((22+5)^2)


f(22) = (1)/((27)^2)


\mathbf{f(22) = (1)/(729)}

f(0) : i.e what is the function when x = 0

So replacing x = 0 into the given function; we have:


f(x) = (1)/((x+5)^2)


f(0) = (1)/((0+5)^2)


\mathbf{f(0) = (1)/((25))}

f(a) : i.e what is the function when x = a

So replacing x = a into the given function; we have:


f(x) = (1)/((x+5)^2)


\mathbf {f(a) = (1)/((a+5)^2)}}

f(tplus+22), i.e what is the function when x = t+22

So replacing x = t+22 into the given function; we have:


f(x) = (1)/((x+5)^2)


f(t+22) = (1)/((t+22+5)^2)


\mathbf{f(t+22) = (1)/((t+27)^2)}

f(xplus+h), i.e what is the function when x =x+h

So replacing x = x+h into the given function; we have:


f(x) = (1)/((x+5)^2)


\mathbf{f(x+h) = (1)/((x+h+5)^2)}

Similarly; another function is given as :

Start Fraction f left parenthesis x plus h right parenthesis minus f left parenthesis x right parenthesis Over h End Fraction f(x+h)-f(x)h.

Mathematically the above function can be expressed as:


(f(x+h)-f(x))/(h)

where ;


f(x+h) = (1)/((x+h+5)^2) and
f(x) = (1)/((x+5)^2)

So;


(f(x+h)-f(x))/(h) = ((1)/((x+h+5)^2) -(1)/((x+5)^2) )/(h)


=( ((x+5^2)-(x+h+5)^2)/((x+h+5)^2(x+5)^2) )/(h)


= (x^2+10x +25-x^2-h^2-25-2xh-10h -10x)/(h(x+h+5)^2-(x+5)^2)


= (h(-h-2x-10))/(h(x+h+5)^2(x+5)^2)


=\mathbf{ (-h-2x-10)/((x+h+5)^2(x+5)^2)}

b) Note that f could also be given by

f(x)equals=StartFraction 1 Over x squared plus 10 x plus 25 EndFraction

1×2+10x+25

Explain what this does to an input number x.

The mathematical expression of the function is:


f(x) = (1)/((x^2+10x + 25))

the input = x ; so 5 is added to the i.e x+ 5;

After that the square of the entity (x+5) is taken giving rise to (x+5)²

then the reciprocal of the function is taken ; which now becomes:


f(x) = (1)/((x+5)^2)

If we expand the quadratic expression in the bracket; we have:

x being multiplied by the square ² which = x²

then x is multiplied by the addition of (5+5 )x to give 10x

Finally 5 is multiplied by the square ² which = 5² = 25

After the addition of all this three together ; the reciprocal was taken to get:


f(x) = (1)/((x^2+10x + 25))

User Klevis Miho
by
4.7k points